Mutation analysis of three genes encoding novel LKB1-interacting proteins, BRG1, STRADalpha, and MO25alpha, in Peutz-Jeghers syndrome. - Alhopuro, P; Katajisto, P; Lehtonen, R; Ylisaukko-Oja, S; Näätsaari, L; Karhu, A; Westerman, A; Wilson, J; de Rooij, F; Vogel, T; Moeslein, G; Tomlinson, I; et al. (2005)
Mutations in LKB1 lead to Peutz-Jeghers syndrome (PJS). However, only a subset of PJS patients harbours LKB1 mutations. We performed a mutation analysis of three genes encoding novel LKB1-interacting proteins, BRG1, STRADalpha, and MO25alpha, in 28 LKB1-negative PJS patients. No disease-causing mutations were detected in the studied genes in PJS patients from different European populations.